The use of Pantherpix pixel detector in radiotherapy QA - Dudas, Denis; Semmler, Milan; Průša, Petr; Neue, Gordon; Koniarova, Irena; Peterkova, Katerina; Gallus, Petr; Koncek, Ondrej; Vrba, Vaclav (Physica medica, 2021)
There are various different detectors, which can be used for radiotherapy measurements, and more are about to be adopted. Hybrid pixel detectors (HPD) have been originally developed for the high energy physics. However, over the last few years they also expanded in the medical physics. Novel 2D detector Pantherpix is a HPD designed specifically for the radiotherapy. In this article, its properties are characterised and an assessment of its use in radiotherapy photon beams is provided. Properties such as response stability, response linearity, angular dependence and energy dependence were studied. In order to prove sufficient clinical quality for relative dosimetry, further measurements were undertaken (i.e. dose profiles and collimator scatter factors). Acquired results were compared with ion chamber and gafchromic film results. Namely the applicability of PhPix for cobalt beam therapy, which is still widely used (and will be used in near future) in economically less developed countries, is considered.
Keywords: Radiometry; Pad detectors; Photon counting detectors; 2D detectors; Radiotherapy Dosage; Radiotherapy QA; Radiotherapy detectors; Hybrid pixel detectors; celková dávka radioterapie; Relative dosimetry; radiometrie